Performance of Traffic Noise Barriers with Varying Cross-Section - Grubeša, Sanja; Domitrović, Hrvoje; Jambrošić, Kristijan (Promet - Traffic&Transportation, 2011)
The efficiency of noise barriers largely depends on their geometry. In this paper, the performance of noise barriers was simulated using the numerical Boundary Element Method (BEM). Traffic noise was particularly considered with its standardized noise spectrum adapted to human hearing. The cross-section of the barriers was varied with the goal of finding the optimum shape in comparison to classical rectangular barriers. The barrier performance was calculated at different receiver points for a fixed barrier height and source position. The magnitude of the insertion loss parameter was used to evaluate the performance change, both in one-third octave bands and as the broadband mean insertion loss value. The proposed barriers of varying cross-section were also compared with a typical T-shape barrier of the same height.